Diseño y simulación de una red WDM inducida al efecto no lineal de la fibra denominado Stimulated Brillouin Scattering. - Calucho Cabrera, Erwin Andrés (2018)
Currently, communication systems have become an essential part of telecommunications, it is necessary to use equipment that supports higher transmission speeds that are coupled to these systems, fiber optic being an ideal medium is affected in its transmission by effect of non linearities. This present research carried out the study and simulation of a network induced to the non-linear effect brillouin stimulated dispersion (SBS) in an optical fiber, to determine the main transmission parameters that impact on the performance of a WDM network. In chapter 1.- The objectives set out to develop the titling work are described, establishing the proposed goals to achieve with the research. Chapter 2.- Describes the background necessary to develop the research, including optical communication systems. Chapter 3.- Details the methodology needed to develop the research. Chapter 4.- Details the SBS effect, which occurs due to the interaction between optical and acoustic waves in a fiber, this defines two scenarios: Scenario 1, it is formed by the transmitter of a single random channel, contains two means of propagation: through an ideal optical fiber and induced to the SBS effect and two receivers with measuring instruments . Scenario 2 consists of a 16-channel transmitter, a multiplexer 16 * 1, contains two means of propagation: through an ideal optical fiber and induced to the SBS effect, demultiplexer 1 * 16 and two receivers with measuring instruments.